A Successful Defence Innovation Ecosystem: To Mark the Work of Colonel József Jáky, Ministerial Commissioner for Air Defence Radar Development - Hajdú, Ferenc (Honvédségi Szemle – Hungarian Defence Review, 2025)
The lessons drawn so far from the Russo-Ukrainian War have shown that the failures of set objectives can be traced back not only to the errors of operational planning but also to shortcomings in the deployability of military equipment in given situations. Change is constant. The quality of (operational or military engineering) responses to the continuously changing situation is a function of the status of the defence innovation ecosystem. Economists, engineers, and doctors are looking to define the concept of innovation differently, based on the ecosystem surrounding them. The defence innovation ecosystem rests on three pillars: the current state of military science, the capabilities of the defence industry, and the defence requirements. Besides these three pillars, the defence innovation ecosystem’s quality is determined by a network of connections among several other elements. What are the elements that need to be operated in the interest of a successful development? What are the connections among these elements? Can one give an exact description of all elements and connections of a defence innovation ecosystem, or does it have some general laws? This study aims to seek the elements of a defence innovation ecosystem required for fighting a successful war through the examination of a successful military technology research and development program: the Hungarian radar developments in the 1940s.